A comprehensive study of structure and properties of nanocrystalline zinc peroxide. (January 2022) - Bocharov, Dmitry; Chesnokov, Andrei; Chikvaidze, George; Gabrusenoks, Jevgenijs; Ignatans, Reinis; Kalendarev, Robert; Krack, Matthias; Kundzins, Karlis; Kuzmin, Alexei; Mironova-Ulmane, Nina; Pudza, Inga; Puust, Laurits; et al.
Abstract: Nanocrystalline zinc peroxide (nano-ZnO2 ) was synthesized through a hydrothermal process and comprehensively studied using several experimental techniques. Its crystal structure was characterized by X-ray diffraction, and the average crystallite size of 22 nm was estimated by Rietveld refinement. The temperature-dependent local environment around zinc atoms was reconstructed using reverse Monte Carlo (RMC) analysis from the Zn K-edge X-ray absorption spectra. The indirect band gap of about 4.6 eV was found using optical absorption spectroscopy. Lattice dynamics of nano-ZnO2 was studied by infrared and Raman spectroscopy. In situ Raman measurements indicate the stability of nano-ZnO2 up to 250 °C above which it decomposes into ZnO and O2 . The obtained experimental results were supported by first-principles density functional theory (DFT) calculations. Highlights: The ZnO2 nanopowder sample was produced by a hydrothermal process. The ZnO2 nanopowder consists of hollow structures with a size of 200–500 nm. The static disorder in nano-ZnO2 dominates significantly the vibrational one. DFT simulations reproduce well electronic and vibrational properties of ZnO2 . Thermal decomposition of ZnO2 to wurtzite ZnO around 250 °C was observed.